Influence of plasma immersion titanium implantation on hydrogenation and mechanical properties of Zr–2.5Nb - Kashkarov E. B. Egor Borisovich; Nikitenkov N. N. Nikolai Nikolaevich; Syrtanov M. S. Maksim Sergeevich; Sutygina A. N. Alina Nikolaevna; Shulepov I. A. Ivan Anisimovich; Lider A. M. Andrey Markovich (2016, 2016)
Title screen